Close-canopy lighting, an effective energy-saving strategy for overhead sole-source LED lighting in indoor farming - Sheibani, Fatemeh; Bourget, Mike; Morrow, Robert C.; Mitchell, Cary A. (Frontiers in Plant Science, 2023)
Significant advancement has been achieved improving electrical efficiency and photon efficacy of light-emitting diodes (LEDs) as the sole source of crop lighting for indoor farming. However, a significant portion of highly efficient photon emissions from improved LEDs is wasted by natural beam spread beyond cropping areas. Additional attention is needed to enhance cropcanopy photon capture efficiency (CCPCE), the fraction of photons emitted from LEDs actually incident upon foliar canopies. We postulate that by taking advantage of unique physical properties of LEDs, such as low radiant heat at photon-emitting surfaces and dimmable photon emissions, reduced vertical separation distance between light-emitting surfaces and lightreceiving surfaces will enhance CCPCE by capturing more obliquely emitted photons that otherwise are lost. This "close-canopy-lighting" (CCL) strategy was tested in two ways: For an energy-efficiency strategy, LEDs were dimmed to the same photosynthetic photon flux density (PPFD) of 160 µmol m -2 s -1 at 45-, 35-, 25-, and 15-cm separation distances between lamps and cropping surfaces. For a yield-enhancement strategy, dimming was not applied, so higher PPFDs occurred at each separation distance closer than 45 cm for the same input energy. In the first strategy, the same biomass of lettuce (Lactuca sativa L. cv. Rouxai) was produced at each separation distance, while significantly lower energy was expended for lighting at each closer separation. Significantly higher biomass was produced at reduced separation distances with the same energy expenditure by LEDs using the yield-enhancement strategy. For both strategies, energy-utilization efficiency (g/kWh) doubled at the closest separation distance of 15 cm compared to the standard 45-cm separation distance. Even higher energy-utilization efficiency was achieved at a 25-cm separation distance when growth compartments were enclosed with a reflective curtain in the yield-enhancement strategy. Our findings suggest that CCL is a highly effective energy-saving strategy for overhead LED lighting, suggesting the need for innovative